Comparative Genomics of Trypanosomatid Parasitic Protozoa - Najib M. El‐Sayed; Myler, Peter J.; Blandin, Gaëlle; Berriman, Matthew; Crabtree, Jonathan; Aggarwal, Gautam; Caler, Elisabet; Renauld, Hubert; Worthey, Elizabeth A.; Hertz-Fowler, Christiane; Ghedin, Elodie; Peacock, Christopher; et al. (ScienceScience, 2005)
A comparison of gene content and genome architecture of Trypanosoma brucei, Trypanosoma cruzi, and Leishmania major, three related pathogens with different life cycles and disease pathology, revealed a conserved core proteome of about 6200 genes in large syntenic polycistronic gene clusters. Many species-specific genes, especially large surface antigen families, occur at nonsyntenic chromosome-internal and subtelomeric regions. Retroelements, structural RNAs, and gene family expansion are often associated with syntenic discontinuities that—along with gene divergence, acquisition and loss, and rearrangement within the syntenic regions—have shaped the genomes of each parasite. Contrary to recent reports, our analyses reveal no evidence that these species are descended from an ancestor that contained a photosynthetic endosymbiont.